Analysis and Prediction of Supply and Demand Risks - Case of the Moroccan Company - El Hiri, Mariam; En-Nadi, Abdelali; Chafi, Anas (International Journal of Supply Chain Management, 2019)
In several entities of the supply chain, a multitude of sources of risk can be a hindrance to companies wishing to have a good level of performance. The purpose of our study is to assess the severity of the several factors that cause supply and demand risks to determine which ones contribute most to the growth of the levels of risks studied. Through the literature review and interviews with logistics and production managers, we identified 16 source factors of the supply and demand risks. In a perspective of improvement of the performance of the supply chain of the Moroccan companies, we have relied on the data of 32 Moroccan companies in order to analyze the criticalities of the 16 factors mentioned in this article, to identify the most critical factors and their impacts on firm objectives, and to deliver a model for predicting the risk levels by a multiple linear regression model.